André Lhote and His International Students - Kuban, Zeynep; Wille, Simone (innsbruck university press, 2020)
Amongst the numerous art academies that existed in Paris between the 1920s and the 1950s, both the liberal as well as the more conservative, the academy of André Lhote (1885-1962), run between 1925 and 1962, was much sought after and attracted an unprecedented number of international students. Due to the excellent state of its archive, it is possible today to acknowledge that almost 1,600 students studied with André Lhote at 18, rue d' Odessa in Montparnasse over the period of four decades, as well as at the field academies that he set up in Mirmande (1926), Gordes (1938) and in Cadiére d'Azur (1948). André Lhote and His International Students is a collection of 13 essays that illuminate the significant way in which André Lhote, through his teaching, his art practice and writing, was responsible for distributing a specific set of formal and theoretical modernist trends. This book thus not only pays tribute to an unjustly neglected artist, theoretician and teacher, but also examines how artists from around the world contributed to and reinterpreted modernist movements that took place in Paris during this period. André Lhote and His International Students is an account of a microcosmic version of the cosmopolitan Paris that was shaped by the flow and circulation of thousands of single artists from around the world.; Zwischen den 1920er und 1950er Jahren existierten in Paris sowohl liberale als auch konservative Kunstakademien. Besonders begehrt war die Académie André Lhote (1885-1962), die von 1925 bis 1962 operierte. Diese zog eine bemerkenswerte Zahl von internationalen Künstlern und Studenten an. Aufgrund des sehr guten Zustands seines Archivs können wir heute davon ausgehen, dass während vier Jahrzehnten an die 1600 Studenten bei André Lhote in Montparnasse, 18 rue d'Odessa und an seinen Landakademien (L'Académie aux champs) in Mirmande (seit 1926), Gordes (seit 1938) und in Cadière d'Azur (seit 1948) studierten. André Lhote and His International Students ist eine Sammlung von 13 Aufsätzen. Diese verweisen auf den bedeutenden Beitrag von André Lhote an der Verbreitung von spezifischen Regeln im Umgang mit formalen und theoretischen modernistischen Trends. Diese Regeln vermochte er sowohl durch seinen Unterricht, aber auch durch seine Kunstpraxis und seine Schriften zu vermitteln. Dabei leistet dieses Buch nicht nur eine Hommage an einen zu Unrecht vernachlässigten Künstler, Theoretiker und Lehrer, sondern untersucht zugleich, wie Künstler aus allen Regionen der Welt durch ihre Aufenthalte in Paris zum Projekt zur künstlerischen Moderne beitrugen und diese re-interpretierten. André Lhote and His International Students ist ein Bericht über eine mikrokosmische Version des kosmopolitischen Paris, welches durch den Fluss und die Zirkulation tausender einzelner Künstler aus der ganzen Welt geprägt wurde.